1998
DOI: 10.1161/01.atv.18.4.562
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 Plasma Levels in a General Population Without Clinical Evidence of Atherosclerosis

Abstract: Abstract-Plasminogen activator inhibitor-1 (PAI-1) plasma levels have been consistently related to a polymorphism (4G/5G) of the PAI-1 gene. The renin-angiotensin pathway plays a role in the regulation of PAI-1 plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
93
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 49 publications
15
93
1
2
Order By: Relevance
“…It has been suggested that this single base-pair polymorphism 675-bp upstream from the start of transcription is functionally important in regulating the expression of the PAI-1 gene and the 4G allele has been associated with increased PAI-1 activity. 10,17 Also chronic smoking has been associated with impaired fibrinolysis in plasma and this largely reflected elevated plasma PAI-1 in smokers. 14 It is interesting that the genetic association of the functional promoter polymorphism in the PAI-1 gene with periodontitis in our study was observed only in the group of non-smokers.…”
Section: Genes and Immunitymentioning
confidence: 99%
“…It has been suggested that this single base-pair polymorphism 675-bp upstream from the start of transcription is functionally important in regulating the expression of the PAI-1 gene and the 4G allele has been associated with increased PAI-1 activity. 10,17 Also chronic smoking has been associated with impaired fibrinolysis in plasma and this largely reflected elevated plasma PAI-1 in smokers. 14 It is interesting that the genetic association of the functional promoter polymorphism in the PAI-1 gene with periodontitis in our study was observed only in the group of non-smokers.…”
Section: Genes and Immunitymentioning
confidence: 99%
“…Since the levels of the selected markers are increased in smokers (Eliasson et al, 1995;de Maat et al, 1996, Miller et al, 1998Margaglione et al, 1998), we hypothesized that reduction of the oxidative stress by tea polyphenols may normalize the increased levels.…”
Section: Introductionmentioning
confidence: 96%
“…Under conditions of cytokine stimulation, the 4G allele had higher activity than the 5G allele. 1 Accordingly, the 4G allele was related to higher plasma PAI-1 antigen levels or activity in most [2][3][4][5] but not all 6 studies in non-Hispanic white populations. However, studies including different ethnic groups, such as Afro-Caribbeans, 7 Asians, 7 Pima Indians, 8 or Japanese, 9 have reported different frequencies of the 4G allele from those in non-Hispanic whites, as well as differences in the relation of the 4G/5G genotype to circulating levels of PAI-1.…”
mentioning
confidence: 94%